Factors Influencing Length of Stay of Forensic Patients: Impact of Clinical and Psychosocial Variables in Medium Secure Setting - Gosek, Paweł; Kotowska, Justyna; Rowińska-Garbień, Elżbieta; Bartczak, Dariusz; Heitzman, Janusz (Frontiers in Psychiatry, 2020)
Objectives: Forensic psychiatric care has two, often contradictory, aims – the treatment of mentally ill offenders and the isolation of the perpetrators to ensure public safety. It is essential to ensure that any periods of liberty deprivation do not last longer than necessary to provide appropriate treatment. Therefore, identifying the factors affecting the length of stay (LoS) is one of the most important research areas in the forensic psychiatry. The literature on this subject is scarce and to date there no data available on LoS for patients in Eastern or Central European patients. Methods: We conducted a retrospective analysis of data for 150 inpatients in a medium secure unit. Based on a literature review and clinical experience, variables potentially influencing LoS were identified and included in the analysis. Results: The variables that were significantly associated with LoS included duration of mental illness; severity of index offence; whether a crime was committed as a result of hallucinations or during drug treatment discontinuation; if the index offences was a continuous crime (crimes committed over an extended period of time); persistent psychosis; multiple antipsychotic treatments; as well as a diagnosis of schizophrenia and schizoaffective disorder. Conclusions: Our findings are highly consistent with observations made by other researchers. However, contrary the majority of previous studies our project incorporates data concerning the clinical presentation of patients. For example, we demonstrate that variables measuring treatment resistance might be one of the crucial determinants of LoS, which is a novel research finding.